Redefining love: Engaging the Johannine and Akan concepts of love through dialogic hermeneutics - Gharbin, Godibert K.; van Eck, Ernest (Hervormde teologiese studies, 2023)
Both the Johannine and Akan cultures are described in scholarly literature as collectivistic communities that value love as a communal value. Nonetheless, a scholarly analysis of the Akan concept reveals that Akan proverbial tradition promotes love motivated by the expectation of reciprocation. Thus, the article aimed to provide a biblical response to these challenges for Akan Christians, who hold love as both a traditional and theological value. Consequently, the study employed Gatti’s dialogic hermeneutics because it encourages engagement between text and culture, viewing them as dialogue partners from which a call to action emanates directed at the interpreter’s context. Even though the Akan concept relates love to sacrifice, forgiveness and reciprocity, it promotes conditional love, thereby diminishing its concept of love-motivated sacrifices and reciprocity. By incarnating the concept of love that Jesus promotes and embodies in John, Akan Christians can establish a culture that reflects the community of God, proscribing conditional love and prescribing utmost and greater love – godly selfless and reciprocal love. In addition, it makes love the substratum of functional unity and interpersonal relationships. Ultimately, it makes love a divine command for the community of believers. Contribution: This article engages the Johannine and the Akan ideations of love through dialogic hermeneutics and, as such, contributes to African biblical hermeneutics and the ongoing discussions on the inculturation of the New Testament within the African context.